Effects of different binder types and concentrations on physical and antioxidant properties of pelleted sweet corn seeds - Nudchara Somrat (2018)
© 2017, Springer-Verlag GmbH Germany. This study investigated the types and concentrations of binders on the physical and antioxidant properties of pelleted sweet corn seeds. Three types of binders at various concentrations (% w/v) were used: carrageenan at 0.1, 0.2 and 0.3; gelatin at 1, 2 and 3%; and gum arabic 0.01, 0.03 and 0.05. The storage periods were 0, 1, 2, 3 and 4 months. The physical properties and qualities of unpelleted and pelleted seeds with non-ionic polyacrylamide (PAM, 5% w/v) were evaluated and compared. The results showed that all three binders were better in pelleting integrity than PAM. Throughout the 4 months’ storage period, pelleted seeds with gum arabic of 0.01% w/v showed that their germination index, seedling growth and shoot growth rates were higher than in unpelleted seeds. The highest amount of anthocyanins, phenolics, carotenoids and the levels of the antioxidant capacities determined by the ferric-reducing antioxidant power, 1,1-diphenyl-2-picrylhydrazyl, and 2, 2-azino-bis (3-ethyl-benzothiazoline-6-sulfonic acid) diammonium salt assays were found in pelleted seeds with gum arabic of 0.01% w/v. The overall quality of seeds depends on their treatment.